Research on epoxy resin curing monitoring using laser ultrasonic. (1st July 2020) - Zhang, Yanjie; Wang, Xiaochen; Yang, Quan; Xue, Renjie; Zhang, Jiamin; Sun, Youzhao; Xu, Dong; Krishnaswamy, Sridhar
Highlights: The curing process of the epoxy resin was monitored using laser ultrasonics. The propagation of ultrasonic in composite and the effect of epoxy curing on ultrasonic characteristics were analyzed. The relationship between amplitude, attenuation coefficient and reflection coefficient was established The effect of curing on frequency dependent attenuation and dispersion was analyzed. Abstract: Adhesive bonding is widely used in the structural assembly of aircraft, and assessing the curing state of the adhesive is important to ensure the safe operation of the assembly. In this paper, the curing process of epoxy resin is monitored by laser ultrasonics. The propagation of ultrasonic waves in a composite structure is discussed, and the curing of epoxy resin and its influence on ultrasonic characteristics are studied. In the fast-drying epoxy resin, the molecular cross-linking rate is fast, the difference of acoustic impedance between the epoxy resin and aluminum gradually decreases, so the transmission coefficient becomes larger and the reflection coefficient decreases. The calculation of absorption attenuation and dispersion should take this change into account. The relationship between amplitude and reflection coefficient is established by far-field ultrasound. The difference in molecular mobility causes the relaxation process, which results in absorption and dispersion of the ultrasonic waves. Making use of the broadband characteristic of laser ultrasonics, the transmission waves are analyzed. As the epoxy resin changes from liquid to solid, the relaxation time is gradually shortened, and the center frequency of the transmitted wave is gradually increased, the absorption attenuation is approximately linear with frequency. The results show that the curing process has a significant effect on ultrasonic characteristics, and laser ultrasonics could be used as an online monitoring method.